2013
DOI: 10.1002/oa.2342
|View full text |Cite
|
Sign up to set email alerts
|

Fruits of Their Labour: Urbanisation, Orchard Crops, and Dental Health in Early Bronze Age Jordan

Abstract: The analysis of dental remains, which outlast most other tissues in the human body, provides insight into past diet, activity patterns and ancestry. The remains from Bab edh‐Dhra' represent the only skeletal sample available to assess the impact of agricultural intensification in the Early Bronze Age of the southern Levant (ca. 3500–2000 bce). This era ushered in a period of ‘urbanisation’, evidenced by fortified towns, planned roadways, developments in irrigation and growing population density. During this ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(53 reference statements)
1
8
0
1
Order By: Relevance
“…Alternatively, such nonlocals may be the result of the growth of the town as people immigrated from neighboring areas, and/or as part of exogamous marriage practices. Finally, while both EB II–III A22 and A55 isotope values contrasted with those of the Early EB II charnel house A56—whose members may have been more invested in pastoral practices, corroborating previous paleoethnobotanical (McCreery, , ) and bioarchaeological studies (Ullinger et al, ) at Bab adh‐Dhra'—the small sample size from A56 precludes any definitive conclusions regarding temporal shifts to subsistence strategies and social organization within the Early Bronze Age on the Dead Sea Plain. More data are required to further explore such questions.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Alternatively, such nonlocals may be the result of the growth of the town as people immigrated from neighboring areas, and/or as part of exogamous marriage practices. Finally, while both EB II–III A22 and A55 isotope values contrasted with those of the Early EB II charnel house A56—whose members may have been more invested in pastoral practices, corroborating previous paleoethnobotanical (McCreery, , ) and bioarchaeological studies (Ullinger et al, ) at Bab adh‐Dhra'—the small sample size from A56 precludes any definitive conclusions regarding temporal shifts to subsistence strategies and social organization within the Early Bronze Age on the Dead Sea Plain. More data are required to further explore such questions.…”
Section: Discussionsupporting
confidence: 77%
“…Excavations and subsequent paleoethnobotanical analyses at Bab adh‐Dhra' have revealed that local populations relied heavily on wheat and barley throughout the EB IA and II–III, although by the latter period, fruits such as grapes and figs grew in importance as part the site's expanding local and regional economies (McCreery, , ). Enhanced dependence on a greater variety of cultigens like fruit was corroborated by Ullinger et al (), who found that while rates of carious lesions did not change over time, an increase in antemortem tooth loss and concomitant decrease in dental wear between the EB IA and II–III periods were indicative of the inclusion of a higher frequency of sticky, soft foods like fruit in the diet.…”
Section: Radiogenic and Stable Isotopes: Accessing Past Lifeways Thromentioning
confidence: 83%
See 2 more Smart Citations
“…Bronze and Iron Age Levantine households engaged in a variety of subsistence strategies spanning a continuum from agriculture to pastoralism (Falconer, ; Lev‐Tov et al, ; Stager, ). Domesticated plant species used by sedentary farmers primarily included C 3 cereals such as wheat and barley but were supplemented by legumes, orchard crops, and edible vine fruits like grapes (Falconer, ; Fall et al, ; Miller, ; Stager, ; Ullinger et al, ). Faunal economies relied chiefly on domesticated sheep and goat, with cattle, pigs, and horse represented in fewer numbers (Falconer, ).…”
Section: Levantine Isotope Signaturesmentioning
confidence: 99%